2011
DOI: 10.1116/1.3604528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanometric roughness on surface properties and fibroblast's initial cytocompatibilities of Ti6AI4V

Abstract: Titanium alloy (Ti6Al4V) has widespread medical applications because of its excellent biocompatibility. Its biological responses can further be enhanced by polishing and passivation. Unfortunately, preparing titanium alloy samples of nanometric roughness is by far much more difficult than preparing those of micrometric roughness, and numerous investigations on roughness induced effects are all focused on micrometric scales. For the remedy, we investigate, at nanometric scale, the influence of roughness on surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…1), while blasted surfaces on machinetooled microthreads show random nanoroughness and somewhat sharp edges. As nano features influence fibroblast behavior and the strength of adhesion through filopodial sensing (Dalby et al 2004;Wang et al 2011), one might speculate that repetitive nanosize surface features created with a laser have the ability to allow fibroblasts to form a physical connective tissue attachment to titanium implants that restricts apical migration of gingival epithelium and preserves the coronal level of bone. While the implications of the marginal bone level are important for the stability of an implant, there are further considerations that relate to the peri-implant soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…1), while blasted surfaces on machinetooled microthreads show random nanoroughness and somewhat sharp edges. As nano features influence fibroblast behavior and the strength of adhesion through filopodial sensing (Dalby et al 2004;Wang et al 2011), one might speculate that repetitive nanosize surface features created with a laser have the ability to allow fibroblasts to form a physical connective tissue attachment to titanium implants that restricts apical migration of gingival epithelium and preserves the coronal level of bone. While the implications of the marginal bone level are important for the stability of an implant, there are further considerations that relate to the peri-implant soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In our results the roughness, wettability, and surface energy did not affect the number of living‐MG63 cells attached in the substrates as the cell attachment test did not show significant differences; however, they conditioned the cell morphology as presented above. In the case of roughness, nanotopography has been a recent focus of investigations due to the fact that molecule interaction, that is the first stage on cell‐biomaterial communication, occurs at this scale 37–40. For instance, Cai et al39 and Webster et al40 have investigated the effect of roughness ( R a parameter from 2 to 40 nm) on protein absorption and cell growth and they have shown that this scale of topography is key to create biomimetic surfaces, which is still an issue in the orthopedic field.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of roughness, nanotopography has been a recent focus of investigations due to the fact that molecule interaction, that is the first stage on cell-biomaterial communication, occurs at this scale. [37][38][39][40] For instance, Cai et al 39 and Webster et al 40 have investigated the effect of roughness (R a parameter from 2 to 40 nm) on protein absorption and cell growth and they have shown that this scale of topography is key to create biomimetic surfaces, which is still an issue in the orthopedic field. In the present study, the obtained results followed the trend exposed by other authors about nanometer scale topography influence on cell morphology 9,10 : the Ti19.1Nb8.8Zr alloy, which is the nano-rougher substrate, induced a flatter cell-shape and extended than the smoother one, the Ti41.2Nb6.1Zr alloy.…”
Section: Cell Behaviormentioning
confidence: 99%
“…Different reasons support this fact. Firstly, roughness is always desirable, as the presence of a certain roughness allows a better gripping of the cell to the surface (although it is well known that nanometric roughness is preferable to micrometric one [19,20]); secondly, a higher specific surface assures a greater possibility of proliferation and a higher cell density for the same apparent surface; and finally, the more significant the quotient between the real surface and the apparent one, the higher the number of vicinities where the precipitation mechanism explained in the previous section can occur. These reasons lead to the expectation of obtaining better osteoblast behaviour for cases with a higher specific surface.…”
Section: Specific Surfacementioning
confidence: 99%